Enhancing EFL Learners’ Writing Skills: Challenges, Strategies, and Pedagogical Insights - Marlina, Marlina (Lembaga Bale Literasi, 2024)
Writing is a critical yet challenging skill for English as a Foreign Language (EFL) learners, requiring mastery of cognitive and linguistic processes. Unlike speaking or listening, writing demands structured articulation, coherence, and grammatical precision, which are compounded by cultural and linguistic differences. This paper explores the complexities of writing in EFL contexts, including learners' struggles with grammar, vocabulary, and rhetorical organization. It highlights the limitations of traditional teaching methods and identifies effective strategies such as process-based approaches, concept mapping, and collaborative learning. The transformative role of technology, particularly data-driven tools like corpora, is also examined. By addressing these challenges, this study proposes practical methodologies to enhance EFL learners' writing competence and recommends pedagogical reforms to bridge gaps in instruction. This research underscores the importance of tailored, innovative approaches in fostering learners' writing proficiency and equipping them for academic and professional success.